Comparative Analysis of Coil and Jacketed Heating Vessels: A Study on Thermal Efficiency and Economic Viability - Alif Aiman Mohamad Alim,; Mustaffa, Norrizal (Research Progress in Mechanical and Manufacturing Engineering, 2024)
The purpose of this study is to determine which configuration of coil and jacketed heating vessels provides the highest levels of thermal efficiency and cost-effectiveness through a comparative analysis. As there were cases of steam leakage through the coil, this leads to the problem statement of the study which is to make an analysis whether the needs of replacing the coil design completely in the industry. This study is limited to using Computational Fluid Dynamics (CFD) simulations to analyse heat distribution and material costs in industrial settings where these kinds of vessel are common. The research uses a methodology that starts with creating and meshing 3D models for every kind of vessel and then simulates the processes of heat transfer inside these models. The study carefully establishes material attributes and boundary conditions that are representative of heating systems that are in use. Contrary to first convictions, the coil design is more complex than anticipated and the jacketed design is marginally more cost-effective, according to the results of the CFD simulations. Additionally, the jacketed vessel marginally surpasses the coil design in terms of thermal efficiency, despite the fact that both designs efficiently transmit heat. The study concludes by suggesting that the jacketed design may provide a better balance between cost and efficiency when choosing a heating vessel for industrial purposes. Coil designs are still competitive, nevertheless, especially in applications where design complexity isn't a barrier. Future study on heating vessel configuration optimisation for improved sustainability and financial viability in industrial applications is made possible by these findings.